Furniture for interior design - Booth, Sam; Plunkett, Drew (London : Laurence King, 2014)
Initial chapters illustrate the different contexts in which furniture is used, from the office and domestic interiors to retail and exhibition space; look at types of furniture, whether off-the-shelf or bespoke; and explore the new vogue for recycling and vintage. Later chapters examine both traditional materials such as wood and the more unusual such as stone and glass, while also explaining new methods of manufacture ? such as Computer Numerical Controlled and Selected Laser Sintering. The final chapter looks at how a design is developed, the site surveyed, prototypes made, and specifications and schedules drawn up
Machine generated contents note: pt. 1 Content And Context -- pt. 2 Types Of Furniture -- pt. 3 Materials And Manufacture -- pt. 4 Working On A Project
Includes bibliographical references (p. 186) and index
Keywords: Furniture design -- Catalogs; Interior decoration; Furniture; Print books